Social organization and control of tuberculosis: the experience of a Brazilian town - Alexandre Favero Bulgarelli; Tereza Cristina Scatena Villa; Ione Carvalho Pinto (Universidade de São Paulo, 2013)
OBJECTIVE: this study was aimed at analyzing the participation of a committee formed by representatives of the community in tuberculosis control based on a participatory management model. METHOD: this is a Case Study involving a tuberculosis committee with data collected through semi-structured interviews conducted with nine individuals. The data, organized through the Association of Ideas Map technique, were analyzed based on the Social Constructionism perspective. RESULTS: the participation of the Tuberculosis Committee studied was shown to be effective and associated with aspects articulated according to the measures taken by the social parties involved in the committee, culminating with assistances inserted into certain parts of the town's co-management. CONCLUSION: it was concluded that the reality of this case study shows that relationships among civil society can guide the management model in the search for effective processes of tuberculosis control.